2011
DOI: 10.1038/bmt.2011.147
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bone mineral density in young adults treated with SCT in childhood: the role of 25-hydroxyvitamin D

Abstract: We measured bone mineral density (BMD) with dualenergy X-ray absorptiometry in the total body, at the lumbar spine, at the femoral neck and in the total hip, in 18 young adults with a median of 18.2 years after SCT. Fifteen patients had undergone auto-SCT and all patients had received TBI. The patients had significantly lower BMD in the total body, at the femoral neck, and in the total hip compared with age-and sex-matched controls. Six of 18 patients (33%) had low bone mass (z-score oÀ1) at one or more measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…Children diagnosed with solid tumors had a higher prevalence of 25(OH)D deficiency (median 61.5%) and insufficiency (median 71%) than those children diagnosed with other type of malignancies, consistent with one large study (n ¼ 2198) of adult oncology patients, which reported a prevalence of 25(OH)D deficiency of 75% [42]. Nevertheless, a few cautionary notes should be mentioned; the small number of studies looking at this population [24,26,36] and their small sample sizes, the seasonality from different studies (often not reported), the different assay methods used to identify 25(OH)D status and the lack of information on intra-assay coefficient of variation, which does not allow us to estimate the validity and reliability of the 25(OH)D results [40]. Additionally, the geographical differences in the prevalence of 25(OH)D levels as well as the discrepancy seen in the representation of childhood diagnosis (Fig.…”
Section: Prevalence Of Plasma Vitamin D Inadequacy and Plasma Parathysupporting
confidence: 64%
See 2 more Smart Citations
“…Children diagnosed with solid tumors had a higher prevalence of 25(OH)D deficiency (median 61.5%) and insufficiency (median 71%) than those children diagnosed with other type of malignancies, consistent with one large study (n ¼ 2198) of adult oncology patients, which reported a prevalence of 25(OH)D deficiency of 75% [42]. Nevertheless, a few cautionary notes should be mentioned; the small number of studies looking at this population [24,26,36] and their small sample sizes, the seasonality from different studies (often not reported), the different assay methods used to identify 25(OH)D status and the lack of information on intra-assay coefficient of variation, which does not allow us to estimate the validity and reliability of the 25(OH)D results [40]. Additionally, the geographical differences in the prevalence of 25(OH)D levels as well as the discrepancy seen in the representation of childhood diagnosis (Fig.…”
Section: Prevalence Of Plasma Vitamin D Inadequacy and Plasma Parathysupporting
confidence: 64%
“…In the USA fortification is discretionary [43,44], whilst in Canada fortification of milk, margarine and plant-based milk is mandatory [44]. An important observation is the difference in the prevalence of vitamin D inadequacy in both Europe and North America between studies from the 1980s and 1990s [23,27,28,31,35] and those published after 2000 [9,24,29,36,38]; with most studies published after 2000 reporting higher prevalence of 25(OH)D than those published before. This could be a reflection of either an increase in 25(OH)D inadequacy in the pediatric oncology population, also seen in the general pediatric population [2,13], or as previously suggested [40], the new more specific assay methods, which are more sensitive to vitamin D metabolites, thus providing more accurate results.…”
Section: Prevalence Of Plasma Vitamin D Inadequacy and Plasma Parathymentioning
confidence: 94%
See 1 more Smart Citation
“…From studies performed at our center on the same individuals in the present SCT group, as well as large studies from other centers, it is abundantly clear that morbidity is very high after SCT, including late endocrinological complications such as growth impairment, growth hormone deficiency, thyroid and sex hormone deficiencies, and infertility . A high prevalence of impaired glucose metabolism, adverse body composition, and other cardiometabolic traits have emerged as novel late complications . Non‐endocrinological complications of SCT that also compromise self‐appreciation of physical roles and limit physical participation are pulmonary and cardiac function abnormalities, cataracts, and skeletal changes such as avascular necrosis, exostoses, and osteoporosis .…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have described bone loss in survivors of pediatric HCT [1,2,4,[20][21][22]. Greater bone loss has been observed in children treated with HCT compared to chemotherapy alone [4].…”
Section: Discussionmentioning
confidence: 99%